Evidence of profound ovarian suppression on combined hormonal contraception resulting in dramatically different ovarian reserve testing and oocyte retrieval outcomes: case report and review of the literature - Chelsea W. Fox, M.D; Jamie Stanhiser, M.D., M.S.C.R; Alexander M. Quaas, M.D., Ph.D (Elsevier, 2020)
Objective: To describe a case report and demonstrate that degree of ovarian suppression with continuous combined hormonal contraception (CHC) may be more profound than previously described and may present similarly as decreased ovarian reserve. Design: Case report and review of the literature. Setting: Private practice in vitro fertilization center. Patient(s): A 36-year-old single gravida 0 presenting for oocyte cryopreservation on CHC. Intervention(s): Discontinuation of vaginal ring combined hormonal contraceptive for 6 months. Main Outcome Measure(s): Antral follicle count, antimüllerian hormone, day 3 follicle-stimulating hormone, total oocytes, and mature oocytes retrieved before and after discontinuation of CHC. Result(s): After a 6-month break from CHC, our patient's antimüllerian hormone level increased from undetectable levels to 3.45 ng/mL, day 3 follicle-stimulating hormone level decreased from 14.9 IU/mL-6.17 IU/mL, and antral follicle count improved from 0-28. In addition, the number of oocytes retrieved after a 4-month CHC break and 6-month break increased from 8 to 29, respectively. Conclusion(s): In patients on long-term combined continuous hormonal contraception, profound ovarian suppression can result in a clinical picture of diminished ovarian reserve and extremely poor response to high-dose stimulation, which may be reversed by more time off from suppression.